Politische Geschichte (Provinzen und Randvölker: Allgemeines ; Britannien, Hispanien, Gallien) - Temporini, Hildegard (Aufstieg und Niedergang der römischen Welt (ANRW) : Geschichte und Kultur Roms im Spiegel der neueren Forschung ; Principat, 2016)
AUFSTIEG UND NIEDERGANG DER RÖMISCHEN WELT (ANRW) is a work of international cooperation in the field ofhistorical scholarship. Its aim is to present all important aspects of the ancient Roman world, as well as its legacy and continued influence in medieval and modern times. The work is divided into three parts: I. From the Origins of Rome to the End of the Republic. II. The Principate. III. Late Antiquity. Each part consists of six systematic sections, which occasionally overlap: 1. Political History, 2. Law, 3. Religion, 4. Language and Literature, 5. Philosophy and the Sciences, 6. The Arts. The articles appear in German, English, French or Italian. For further information about the project and to view the table of contents of earlier volumes please visit.